2022
DOI: 10.1177/21925682221103530
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Elective Spine Surgery for Medicaid Beneficiaries: A Systematic Review

Abstract: Study Design Systematic review Objectives We sought to synthesize the literature investigating the disparities that Medicaid patients sustain with regards to 2 types of elective spine surgery, lumbar fusion (LF) and anterior cervical discectomy and fusion (ACDF). Methods Our review was constructed in accordance with Preferred Reporting Items and Meta-analyses (PRISMA) guidelines and protocol. We systematically searched PubMed, Embase, Scopus, CINAHL, and Web of Science databases. We included studies comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
(198 reference statements)
2
16
1
Order By: Relevance
“…[34][35][36][37]40,41 As previously discussed by multiple groups, postoperative ED utilization was increased in patients undergoing various orthopedic interventions for those considered to be living in disparaged socioeconomic conditions. [34][35][36][37] This increased utilization potentially are responsible for the increased expenditures as patients would be utilizing emergency health care services at a greater rate, and therefore could accumulate higher expenses. Another factor that could be responsible for the increased health care expenditures involves the location of the surgery and whether it is inpatient or outpatient.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…[34][35][36][37]40,41 As previously discussed by multiple groups, postoperative ED utilization was increased in patients undergoing various orthopedic interventions for those considered to be living in disparaged socioeconomic conditions. [34][35][36][37] This increased utilization potentially are responsible for the increased expenditures as patients would be utilizing emergency health care services at a greater rate, and therefore could accumulate higher expenses. Another factor that could be responsible for the increased health care expenditures involves the location of the surgery and whether it is inpatient or outpatient.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, Lieber et al 33 , using the National Inpatient Sample database, isolated patients undergoing primary 1-to 2-level The greater ED utilization, among patients living in greater deprivation indices, in this study are agreeable with what was reported in prior investigations (9.67% vs. 8.91%; OR: 1.10, 95% CI, 1.02-1.18, P = 0.014). [34][35][36][37] Jain et al 34 completed a study using the PearlDiver database from the years 2007 to 2015, isolating patients who underwent primary lumbar fusion and found increased odds for ED utilization within 30 days, postoperatively (adjusted OR: 1.42, 95% CI, 1.28-1.57, P < 0.001). It should be noted that although Jain and colleagues found increased odds for ED utilization after lumbar fusion, they utilized a 30-day follow-up period, whereas this study used a 90-day follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that different payor types are associated with different rates of complication following various orthopedic procedures and surgeries. For example, a systematic review of spine surgeries determined that patients with Medicaid insurance were associated with decreased access to surgery, lower reimbursement rates, and worse health-care outcomes than non-Medicaid patients [ 4 ]. Furthermore, a study by Kim et al.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A body of literature including a recent systematic review has demonstrated wide disparities with regard to access and outcomes in patients with Medicaid insurance undergoing spine surgery. 3 Medicaid and other public plans pay providers substantially lower rates for health services rendered compared with commercial plans. 4 Among commercial insurance plans, which are largely employer sponsored, there is variation in plan structure.…”
mentioning
confidence: 99%
“…In the United States, disparities exist in access to surgical care and perioperative outcomes based on patient insurance status 1,2 . A body of literature including a recent systematic review has demonstrated wide disparities with regard to access and outcomes in patients with Medicaid insurance undergoing spine surgery 3 . Medicaid and other public plans pay providers substantially lower rates for health services rendered compared with commercial plans 4 …”
mentioning
confidence: 99%